Investigating the impact of inflation on labour wages in Construction Industry of Malaysia - Wesam Salah Alaloul; Muhammad Ali Musarat; M.S. Liew; Abdul Hannan Qureshi; Ahsen Maqsoom (Ain Shams Engineering Journal, 2021)
Labours in construction are one of the main pillars in the construction industry of Malaysia for projects execution. Construction labours not only contributes to the development of the construction industry but also impacts the Malaysian economy. Consideration of labour wages is made in the initial phase of the project budget, however, wages are getting changed over time. The inflation rate is one of the key factors which affect labours wages. Regrettably, the inflation rate is being ignored while computing labour wages for projects budget development, resulting in cost overrun of construction projects. In this regard, the correlation coefficient test was used to determine the impact of the inflation rate on labour wages gathered from the year 2013 to 2019. The results showed that a significant acceptable relationship exists among the inflation rate and several categories of labour wages. Most of the labour wages showed a negative relationship with the inflation rate, indicating the deviation in the wages, thus, result in cost overrun. To steer the cost overrun effect, it is recommended to adopt automation system and introduce the Industrial Revolution (IR) 4.0 in construction projects as a replacer of labours.